A comparison of endogenous and exogenous timing in a social learning experiment - Lukas Meub; Till Proeger; Hendrik Hüning (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2013)
This paper experimentally investigates social learning in a two-agent prediction game with both exogenous and endogenous ordering of decisions and a continuous action space. Given that individuals regularly fail to apply rational timing, we refrain from implementing optimal timing of decisions conditional on signal strength. This always renders it optimal to outwait the other player regardless of private signals and induces a gamble on the optimal timing and action. In this setting, we compare exogenous and endogenous ordering in terms of informational efficiency, strategic delay and social welfare. We find that more efficient observational learning leads to more accurate predictions in the endogenous treatments and increases informational efficiency compared to the benchmark exogenous treatment. Overall, subjects act sensitively to waiting costs, with higher costs fostering earlier decisions that reduce informational efficiency. For a simple implementation of waiting costs, subjects more successfully internalize information externalities by adjusting their timing according to signal strength. Simultaneous decisions in endogenous ordering avoid observational learning and compensate the higher degree of rational decisions. Overall, endogenous timing has no net effect on social welfare, as gains in accuracy are fully compensated by waiting costs. Our results hold relevance for social learning environments characterized by a continuous action space and the endogenous timing of decisions.
Keywords: C91; D82; D83; 330; Endogenous Timing; Information Externalities; Laboratory Experiment; Social Learning; Strategic Delay